Copper-doped ZrO2 nanoparticles as high-performance catalysts for efficient removal of toxic organic pollutants and stable solar water oxidation. (15th April 2020) - Reddy, Ch Venkata; Reddy, I. Neelakanta; Ravindranadh, K.; Reddy, Kakarla Raghava; Shetti, Nagaraj P.; Kim, D.; Shim, J.; Aminabhavi, Tejraj M.
Abstract: Doping effect on the photoelectrochemical (PEC) water splitting efficiency and photocatalytic activities of ZrO2 under visible light are reported. The XRD analysis revealed that pure, 0.1 and 0.3 mol% doped samples showed mixed crystal phases (tetragonal and monoclinic) and 0.5 mol% doped sample showed a pure tetragonal phase. Under visible light, 90% of methyl orange dye degradation was achieved with in 100 min. Moreover, the optimal doped sample showed a significant degradation rate constant over other samples. The doped photoelectrodes display a better PEC water oxidation performance over pure photoelectrode. Furthermore, the optimal doped (0.3 mol %) electrode shows 0.644 mAcm −2 photocurrent density, corresponding to an approximate 50-fold enhancement over pure electrode (0.013 mAcm −2 ). The optimized doped sample achieved 98% degradation of methyl orange within 100 min of light irradiation. The superior PEC water oxidation and photocatalytic activity of optimal doped samples under visible light are credited to suitable doping content, crystalline size, greater surface area, suitable bandgap, a lower charge carrying resistance, surface properties and the ability for decreasing the charge carrier's recombination rate. Highlights: Doping effect on efficient removal of organic dyes and the PEC water splitting are reported. The band gap values reduced from 5.02 to 2.1 eV as the doping concentration increased. The optimal doped sample achieved 90% methyl orange dye degradation under solar light. The EIS analysis revealed the optimal doped sample exhibited the lower charge resistance. The optimal photocatalysts showed 50-fold enhancement in photocurrent density over pure sample.